Mixed Choir and Instruments in the Composition of the Worship Music of the Stations of the Cross (Harmonia: Journal of Arts Research and Education, 2020)
The station of the cross is an event of the Passion story of Jesus Christ carrying the cross from the Pilate’s palace to the hill of Golgotha. On that journey, Jesus endured torture and humiliation, both from Roman soldiers and Jews. Based on this story, the objective of the research is to describe the process of developing a new compositional composition based on the story of the journey in the format of a choir and a musical ensemble. The research method used in this research is descriptive qualitative. Data collection was carried out through observation, interviews, and documents. After all data has been collected, the next process is to determine the use of scales, instrumentation, and composition based on rhythmic and melodic motifs, time signature, key signature, tempo, and composition of song texts. The choice of musical signs is adjusted to the meaning of the lyrics used. The composition of the Song of the Station of the Cross which is composed is a combination of a mixed choir consisting of soprano, alto, tenor, and bass with a musical ensemble. The novelty of the composition of the Song of the Station the Cross lies in the use of the style of baroque passions (1600-1750), aria, and recitative combined with modern harmonies, namely the use of the seventh tone, the ninth tone, and the thirteenth tone of a chord, and the use of Indonesian as the whole text of the composition